Inclusive conversations : fostering equity, empathy, and belonging across differences - Winters, Mary-Frances (Berrett-Koehler Publishers, 2020)
"What is impressive is not only how Winters builds a case for the urgency and need for bold, inclusive conversations but that she also gives specific strategies and competencies to turn her theory into practice." -Dr. Sheila Robinson, publisher and CEO, Diversity Woman Media Effective dialogue across different dimensions of diversity, such as race, gender, age, religion, or sexual orientation, fosters a sense of belonging and inclusion, which in turn leads to greater productivity, performance, and innovation. Whether in the workplace, faith communities, or educational settings, our differences can tear us apart rather than bring us together if we do not know how to communicate. Recognizing our collective responsibility to earnestly address our differences and increase understanding and empathy will not only enhance organizational goals but will also lead to a healthier, kinder, and more compassionate world. Award-winning diversity, equity, and inclusion consultant Mary-Frances Winters has been leading workshops on what she calls Bold, Inclusive Conversations for years. In this book she offers specific dialogue strategies to foster greater understanding on the following topics: • Recognizing the importance of creating equity and sharing power • Dealing with the "fragility" of dominant groups--their discomfort in engaging with historically subordinated groups • Addressing the exhaustion historically marginalized groups feel from constantly explaining their different lived experience • Exploring how to build trust and create psychologically safe spaces for dialogue This guide is comprehensive for anyone who wants to break down the barriers that separate us and facilitate discussions on potentially polarizing topics.